The Historical novel in the book " Elite Times in the Wonders of land and sea" For sheikh of Al-Rabwa Al-Dimashqi - Hussein, Wasan Ibrahim (Al-Adab Journal, 2022)
A book Containing non geographical art such as historya Stratigraphy, Mineralogy anthropology, Zoology and archeology and others, He is despite his Portrayal of the case of the levant in the Seventh and eighth century that toured all of it was not limited in the geography of Egypt for this purpose, we find him stuffing his book with wonders and oddities, especially with regard to antiquities. However, in history he transmits many stories from Al-Bakri, Ibn Al-Alheer and other historians.